Design of Robust Controller for a Class of Uncertain Discrete-Time Systems Subject to Actuator Saturation - Binazadeh, Tahereh; Bahmani, Majid (IEEE transactions on automatic control, 2017)
This technical note studies the robust output tracking controller design for a class of uncertain discrete-time systems subject to actuator saturation. To achieve this capability, a new controller is proposed by robustifying the discrete-time composite nonlinear feedback (DCNF) control law. Since, the proposed controller may be saturated; a precise analysis is done to show its robust performance in spite of presence of actuator saturation and time-varying external disturbances. Additionally, a theorem is given and proved which guarantees the disturbance attenuation via the proposed control law for three different cases of the saturation function and it is shown that even if the control signal is saturated, the proposed controller achieves steady-state error of order O(T) for state regulation. Finally, computer simulations are performed for a practical system and the applicability of the proposed controller is shown.